1982
DOI: 10.1002/jcp.1041130117
|View full text |Cite
|
Sign up to set email alerts
|

Transcription of chick genes by mammalian RNA polymerase II in chick erythrocyte‐mammalian cell heterokaryons

Abstract: The introduction of chick erythrocyte nuclei into mammalian cell cytoplasms results in their reactivation as evidenced by the de novo transcription of chick genes and the synthesis of both globin and constitutive proteins. In the present study, chick erythrocytes have been fused to L6 rat myoblasts and to alpha-amanitin-resistant variants of L6 to determine whether the chick or the mammalian RNA polymerase II was responsible for transcription of chick genes. Heterokaryons formed by fusing chick erythrocytes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
1

Year Published

1982
1982
2004
2004

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 33 publications
1
0
1
Order By: Relevance
“…Recent evidence indicates that in heterokaryons rat RNA polymerase II is actively transcribing the chick genome (16). Our present results suggest but do not prove that rat polymerase of type I is actually transcribing the chick rRNA genes.…”
Section: Resultscontrasting
confidence: 97%
See 1 more Smart Citation
“…Recent evidence indicates that in heterokaryons rat RNA polymerase II is actively transcribing the chick genome (16). Our present results suggest but do not prove that rat polymerase of type I is actually transcribing the chick rRNA genes.…”
Section: Resultscontrasting
confidence: 97%
“…The time and location of polymerase-I-antigenicity agree also with the appearance of a-amanitin-resistant RNA polymerase activity (14) as detected by a cytochemical assay based on incubation with labeled nucleoside triphosphates and drugs (15). Using this type of assay as well as biochemical techniques, we recently demonstrated that rat RNA polymerase II enters the nucleoplasm of chick nuclei in rat-chick heterokaryons and is active in transcribing some of the chick globin genes (16). We conclude that during reactivation mammalian RNA polymerases of the types I and II migrate into the chick erythrocyte nuclei and become distributed in their respective subeompartments.…”
Section: Resultssupporting
confidence: 53%